Management and Transactional Analysis Approach in Group Counseling - Nila Frischa Panzola; Netrawati; Zadrian Ardi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The purpose of this study is to explore the application of Transactional Analysis in the context of group counseling. Transactional Analysis, developed by Eric Berne, is a psychological theory that examines social interactions to understand and improve interpersonal communication. In group counseling, transactional analysis is used to help group members recognize and change unhealthy or dysfunctional interaction patterns. This approach identifies three main aspects of a person’s ego: Parent, Adult, and Child, and how each of these aspects influences behavior and communication. This article reviews transactional analysis techniques such as therapeutic contracts, structural analysis, transactional analysis, life script analysis, and psychological games that often emerge in group interactions. Using case studies and practical application examples, this article demonstrates how transactional analysis can improve self-awareness, communication skills, and overall group dynamics. The results suggest that the use of transactional analysis in group counseling not only helps individuals address personal issues but also improves group effectiveness through a deeper understanding of the interactions and motivations behind behavior.